Differences in Cerebrospinal Fluid Glucose Levels in Meningitis Patients Based on Examination Time: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Haryando, Herpika Septi; Elfira Yusri; Desywar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Cerebrospinal fluid (CSF) is a vital fluid in the central nervous system that can provide important diagnostic information, especially in cases of meningitis. CSF glucose is one of the key parameters that can help in the diagnosis and monitoring of the patient's condition. However, the stability of glucose in the CSF after sampling is of concern due to the potential for levels to decrease over time. Methods: This cross-sectional analytical observational study was conducted at Dr. M. Djamil General Hospital Padang between May and August 2023. CSF samples from patients with suspected meningitis were checked for glucose levels at three time points: the first 1 hour, 2 hours, and 4 hours after sample collection. Patients with puncture trauma and late delivery of samples (more than 30 minutes) were excluded. Results: This study involved [number of patients] CSF samples that met the inclusion criteria. The mean decrease in CSF glucose levels between the 1-hour and 2-hour examination was 5.667 mg/dL (±0.75 mg/dL), while between 1 hour and 4 hours, it was 12.183 mg/dL (±1.549 mg/dL). Statistical analysis showed significant differences (p < 0.001) between the three examination time points. Conclusion: Glucose levels in the CSF of meningitis patients decreased significantly over time after sampling. This emphasizes the importance of checking CSF glucose as soon as possible to obtain accurate results and avoid misinterpretation in the diagnosis and treatment of meningitis.